2017
DOI: 10.1007/s40368-016-0262-8
|View full text |Cite
|
Sign up to set email alerts
|

The opinion of children and their parents about four different types of dental restorations in a public health service in Brazil

Abstract: A high degree of satisfaction was observed with children and their parents in the four types of restoration after placement. However, if it could be chosen in advance, children prefer the PMCs and parents a tooth-coloured material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
2
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 9 publications
4
29
2
2
Order By: Relevance
“… 9 Perhaps clinicians prefer HTPMCs because it has been found that children's behaviour was better compared to a more traditional approach. 14 One very recent study 15 found that children preferred crowns to restorations, and parents preferred tooth coloured restorations. Perhaps the only downside to HTPMCs is their appearance.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Perhaps clinicians prefer HTPMCs because it has been found that children's behaviour was better compared to a more traditional approach. 14 One very recent study 15 found that children preferred crowns to restorations, and parents preferred tooth coloured restorations. Perhaps the only downside to HTPMCs is their appearance.…”
Section: Introductionmentioning
confidence: 99%
“…Results of this trial showed a good level of crowns acceptance, with 88% of parents being “very satisfied” with the procedure. In addition, children seem to like the appearance of SSCs, tending to prefer a crown to other commonly used restorative materials . It can be assumed that the appearance of metal crowns might be of more concern to aesthetically orientated clinicians rather than to carers or children.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, children seem to like the appearance of SSCs, tending to prefer a crown to other commonly used restorative materials. 23 It can be assumed that the appearance of metal crowns might be of more concern to aesthetically orientated clinicians rather than to carers or children. On the other hand, it has been suggested that dentists' reluctance to use SSCs as part of their regular treatment may be linked to factors such as low financial remuneration or perceived difficulties in placing SSCs.…”
Section: Discussionmentioning
confidence: 99%
“…5 In a study comparing amalgam, composite resin and atraumatic restorations with stainless steel crowns installed by Hall Technique with respect to parents' and patients' opinion, all restorations performed satisfactorily but children preferred the stainless steel crowns while parents preferred esthetic restorations. 16 Longevity of the stainless steel crowns installed according to the Hall technique protocol has also been investigated. A randomized split-mouth clinical study compared the performance of conventional composite resin restorations (CRRs) and prefabricated stainless steel crowns (PSCs) installed by Hall Technique.…”
Section: Discussionmentioning
confidence: 99%